Dynamics and Growth Projections of Fintech Sharia Lending (Sharia and Conventional) in Indonesia: Spatial-Temporal Analysis and Policy Implications: Dinamika dan Proyeksi Pertumbuhan Fintech Syariah Lending (Syariah dan Konvensional ) di Indonesia: Analisis Spasial-Temporal dan Implikasi Kebijakan - Sulhan; Hamzah, Moh (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2024)
Fintech lending in Indonesia is experiencing rapid growth, but there are significant variations in growth dynamics between Java, outside Java, and overseas segments. This study aims to explore and project the growth patterns of Islamic and conventional fintech using spatial-temporal analysis. Quantitative research methods were applied with data analysis of the number of lender accounts and funds disbursed from January 2022 to May 2024. Results show that Java experienced market consolidation with an increase in disbursed funds, while outside Java showed moderate growth, and the overseas segment experienced high fluctuations but with significant expansion potential. Policy implications include the need for increased penetration outside Java, development of a cross-border regulatory framework, and incentives for fintech innovation. The findings highlight the importance of diversified policies to support inclusive growth and stability of the national financial system.